1979
DOI: 10.1002/chin.197935207
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: AZIRIDINES. PART II. SYNTHESIS OF 1‐ALKYL‐2,3‐DIPHENYLAZIRIDINES BY GABRIEL′S S METHOD

Abstract: Die Chlorierung der erythro‐ und threo‐Formen der Alkohole (I) liefert die Chloride (II) ausschließlich in der threo‐Fonn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Thiobenzophenone (2a) [28], 2,2,4,4-tetramethyl-3-thioxocyclobutanone (2b) [29], and adamantanethione (2c) [30] were obtained according to published procedures. trans-1-Methyl-2,3-diphenylaziridine (trans-1a) was prepared from erythro-2-(methylamino)-1,2-diphenylethanol by treatment with Ph 3 P/CCl 4 /Et 3 N, according to a known procedure [19], as well as cis-1a [31] and cis-1,2,3-triphenylaziridine (cis-1b) [32]. Dimethyl dicyanofumarate (DCFM; 7a) was synthesized from methyl cyanoacetate and SOCl 2 [16].…”
Section: Methodsmentioning
confidence: 99%
“…Thiobenzophenone (2a) [28], 2,2,4,4-tetramethyl-3-thioxocyclobutanone (2b) [29], and adamantanethione (2c) [30] were obtained according to published procedures. trans-1-Methyl-2,3-diphenylaziridine (trans-1a) was prepared from erythro-2-(methylamino)-1,2-diphenylethanol by treatment with Ph 3 P/CCl 4 /Et 3 N, according to a known procedure [19], as well as cis-1a [31] and cis-1,2,3-triphenylaziridine (cis-1b) [32]. Dimethyl dicyanofumarate (DCFM; 7a) was synthesized from methyl cyanoacetate and SOCl 2 [16].…”
Section: Methodsmentioning
confidence: 99%
“…1:1, which in the 1 H-NMR spectrum showed, in addition 2 ) Thionyl chloride (SOCl 2 ) was used as the chlorinating agent and Et 3 N as the base. The starting material was consumed, but only a complex a mixture of products was obtained [8].…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, trifluoromethylsubstituted -amino alcohols were explored as convenient substrates for the preparation of aziridines with a new substitution pattern. First attempts were made following Gabriel's method, which is based on the initial conversion of a -amino alcohol to the corresponding -halo amine and subsequent treatment with a base [8]. In the case of 4b (Ar = Ph, R =t-Bu), the attempted synthesis of the aziridine was unsuccessful 2 ).…”
Section: Fig 1 Ortep-plotmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] The thermal fragmentation of b-lactams occurs by two different pathways, the rst one gives the starting ketene and imine (B) and the second pathway (A) gives alkene and isocyanate which could be trapped with amine to give the corresponding urea derivatives, Fischer found that the thermal fragmentation favours pathway A, while photolysis favours pathway B (Scheme 1).…”
Section: -35mentioning
confidence: 99%